A MICROSTRUCTURAL ANALYSIS USING BEM FOR VISCOELASTIC MATERIALS - Furtado, Daniel Canongia; Arroyave, Adrián Alberto Betancur; Anflor, Carla Tatiana Mota (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Composite materials are mixtures of two or more different materials, in order to improve the mechanicals properties. Mixtures of different materials can provide the appropriate behavior for a given solicitation. This behavior can be verified by the means of homogenization techniques. In this sense, the main goal of this work relies on establishing a homogenization methodology for viscoelastic composites using boundary elements method (BEM). For the homogenization process, was considered the average strain in each stressstrain curve. The experimental data were obtained from the literature. The representative volume element (RVE) was defined based on the calculated mean strains. For each volume element (EV) a twenty creep tests were conducted varying the positions of the microstructural heterogeneities. Mean, standard deviation and coefficient of variation (CV) were estimated for each EV. Finally, a graph of the number of inclusions x coefficient of variation is presented for each test. The numerical final results showed good agreement with experimental data reported in the literature.